2017
DOI: 10.1016/j.cdtm.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 627 patients with right‐ and left‐sided colon cancer in China: Differences in clinicopathology, recurrence, and survival

Abstract: ObjectiveRecent studies have reported increased mortality for right-sided colon cancers; however, the results are conflicting for different stage tumors. We examined the differences in clinicopathology between right- and left-sided colon cancers and the relationships between colon cancer location (right- and left-side) and 5-year disease-free survival (DFS) and overall survival (OS).MethodsWe identified patients from 2005 to 2008 with stage II/III colon cancer who underwent surgery for curative intent. We expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 37 publications
3
24
1
2
Order By: Relevance
“…Moreover, a meta-analysis concluded that in the right-sided advanced CRC, chemotherapy plus bevacizumab was a treatment option [44,45]. Moreover, the higher antigenic load described in the right-sided tumors is more likely to be due to the defective mismatch repair mechanism because of the high frequency of mutations, thus increasing the possibility of immune recognition [46,47]. Lim DR et al described data from 414 patients under curative resection for right or left-sided colon cancer, suggesting that patients with left-sided tumors had a better survival outcome than those with right-sided tumors, especially in stage III patients [41].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a meta-analysis concluded that in the right-sided advanced CRC, chemotherapy plus bevacizumab was a treatment option [44,45]. Moreover, the higher antigenic load described in the right-sided tumors is more likely to be due to the defective mismatch repair mechanism because of the high frequency of mutations, thus increasing the possibility of immune recognition [46,47]. Lim DR et al described data from 414 patients under curative resection for right or left-sided colon cancer, suggesting that patients with left-sided tumors had a better survival outcome than those with right-sided tumors, especially in stage III patients [41].…”
Section: Discussionmentioning
confidence: 99%
“…Right-sided location, female sex, T4 disease, lymph node metastasis, and perineural invasion are independent risk factors for the locoregional recurrence of colon cancer (60). Qin et al (61) found that right-and left-sided colon cancer had significantly different clinicopathological characteristics. Right-sided colon cancer had a higher incidence of recurrence than left-sided colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan-Meier survival analysis of the patients divided according to localization shows an overall five-year survival rate of 62% in patients with right colon cancer compared to 72% in patients with left colon cancer. as opposed to these results, many studies prove that the right colorectal cancer is more often in an advanced stage, whereas the left colorectal cancer is diagnosed in earlier stages (3,4,8,9,12).…”
Section: Discussionmentioning
confidence: 89%
“…in 2012 the incidence rate of colorectal cancer was 44,2/100000 in men, and 24,7/100000 in women; the mortality rate in men was 26,7/100000, and in women 24,7/100000. colorectal cancer is among ten most common causes of death in osijek-Baranya county; it was ranked fourth with 158 deaths in 2016 (1,4,5,10,11).…”
Section: Introductionmentioning
confidence: 99%